Modifikasi Metode Iterasi Behl Tanpa Turunan Kedua Dengan Orde Konvergensi Optimal - Wartono Wartono; Mohammad Soleh (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
Behl iterative method is a third-order of iterative method with three evaluation of functions for solving nonlinear equation. This paper discuss a modification of Behl iterative method by reduced second derivative using hiperbolic function. The aim of this modification is to improve the order of convergence by keep the number of functional evalutions. The result od study shows that the new iterative method has a fourth-order of convergence and requires three evalualions of funtion with efficiency index as 41/3 » 1,5874. Numerical simulation is given by using six real functions to test the performance of the modification of Behl method which includes number of iterations, evaluation of function, and absolute error. The performance of new method is compared with Newton method, Newton-Steffensen, Chun-Kim method, and Behl’s method. The result of numerical simulation shows that the performance of the modification of Behl’s method is better than others. Keyword: Behl method, order of convergence, efficiency index, evaluation of function, numerical simulation